Analyse der Tätigkeitsstruktur bayerischer Schulpsychologen - Lehmeier, Heinz [Verfasser] (My University, 1995)
"An analysis of the work reports of Bavarian school psychologists shows an activity structure in which individual counselling still occupies the lion's share of work time, i.e. on average ca. 50%. This result is valid independent of the type of school or the number of pupils for which the school psychologist is responsible. By and large the activity profiles of school psychologists as regards the types of school examined show only few differences. An examination of those activities which can be categorized under the term system- oriented consultation proves that, contrary to frequent calls for such an approach in subject literature, most school psychologists are active in this field only to a limited degree. Measures which are clearly directed at bringing about qualitative changes in a school remain exceptions. The preconditions needed to create a more balanced long-term approach between individual counselling and system-oriented consultation are considered on a social and institutional level as well as concerning the expectations of the clientele and the practice-orientation of the school psychologists themselves." (author's abstract, IAB-Doku) ((en)) "Eine Analyse der Tätigkeitsberichte bayerischer Schulpsychologen ergibt, dass nach wie vor die Einzelfallberatung mit durchschnittlich ca. 50% den Löwenanteil an der Gesamtarbeitszeit in Anspruch nimmt. Dies gilt unabhängig von der Schulart sowie der Anzahl der Schüler im Einzugsbereich einzelner Schulpsychologen. Die Tätigkeitsprofile der Schulpsychologen unterscheiden sich bei den untersuchten Schularten nur geringfügig. Die Untersuchung der unter dem Begriff Systemberatung zu fassenden Tätigkeitsmerkmale zeigt, dass, im Unterschied zu zahlreichen Forderungen in der Fachliteratur, die meisten Schulpsychologen nur in sehr geringem Umfang systemberaterisch tätig werden. Voraussetzungen, die längerfristig ein ausgewogeneres Verhältnis von Einzelfall- und Systemberatung herbeiführen könnten, müssten sich auf gesellschaftlicher und institutioneller Ebene, hinsichtlich der Erwartungshaltung der Klientel sowie in der Handlungsorientierung der Schulpsychologen selbst einstellen." (Autorenreferat, IAB-Doku)
Keywords: P 3.1.2 Psychologen; I 2.1.2.3 Bayern; Psychologe; Schulpsychologe; Berufsproblem; Tätigkeitsmerkmal; Bayern; 1990-1991